GaAs integrated quantum photonics: Towards compact and multi‐functional quantum photonic integrated circuits. Issue 6 (14th September 2016) - Dietrich, Christof P.; Fiore, Andrea; Thompson, Mark G.; Kamp, Martin; Höfling, Sven
Abstract : The authors provide an overview of the recent progress and challenges in quantum integrated photonic components and circuits based on the GaAs technology platform. All key functionalities, including single‐photon sources and detectors, photon‐number‐resolving detectors, integrated autocorrelators and tunable Mach–Zehnder interferometers have been realized and tested, and on‐chip photon–photon interference has been demonstrated. Abstract: The recent progress in integrated quantum optics has set the stage for the development of an integrated platform for quantum information processing with photons, with potential applications in quantum simulation. Among the different material platforms being investigated, direct‐bandgap semiconductors and particularly gallium arsenide (GaAs) offer the widest range of functionalities, including single‐ and entangled‐photon generation by radiative recombination, low‐loss routing, electro‐optic modulation and single‐photon detection. This paper reviews the recent progress in the development of the key building blocks for GaAs quantum photonics and the perspectives for their full integration in a fully‐functional and densely integrated quantum photonic circuit.